Assessment of Clinical Factors in the Evolution of Heart Transplant Patients: A Single-Center Retrospective Cohort Study - Paula, Gabriela Vieira de (2024)
Introduction: After heart transplantation (HTx), some patients continue to experience disproportionately high mortality. Objectives: To investigate which clinical variables are associated with survival after HTx. Methods: Retrospective, single-center cohort study with 55 patients undergoing HTx from May 2019 to April 2023. Results: Logistic regression identified, as variables associated with death, the increase in creatinine in the immediate postoperative period ( POI) (p = 0.0067), pulmonary vascular resistance (RVP) (p = 0.0185) and pulmonary artery systolic pressure (PSAP) before Htx (p = 0.0415). When constructing the ROC curve (receiver operating characteristic curve) with the delta of the increase in creatinine in the first 24 postoperative hours, the cutoff point was 0.35 mg/dL, the sensitivity was 0.76, and the specificity was 0. 90. In the ROC curve for PVR, the cutoff point was 2.23 Woods units (WU), with sensitivity of 0.79 and specificity of 0.72. In the ROC curve for PSAP, the cutoff point was 40.50 mmHg, with a sensitivity of 0.89 and a specificity of 0.86. Conclusion: An increase in creatinine to a value greater than or equal to 0.35 mg/dL in the first 24 hours, PSAP with values greater than 40.5 mmHg and an increase in RVP to a value above 2.23 WU are associated with increased rates of hospital mortality after HTx.